From classroom goal structures to academic outcomes: The mediating role of expectancy-value beliefs in adolescent learning: From classroom goal structures to academic outcomes: the mediating role of expectancy-value beliefs in adolescent learning - Zhang, Linjia; Mendoza, Norman B.; Jiang, Yi (European journal of psychology of education, 2025)
Students’ perceptions of the classroom environment are critical determinants of their motivation and academic success. However, the psychological mechanisms through which these contextual factors influence academic outcomes remain insufficiently explored, particularly in different subject domains. Grounded in the Situated Expectancy-Value Theory, this study examined the role of classroom goal structures in predicting adolescent students’ expectancy-value beliefs and their subsequent academic outcomes in Mathematics and English. Using structural equation modeling with data from 634 Chinese secondary school students, our findings reveal both general and domain-specific patterns. Specifically, self-efficacy positively mediated the predictive paths from classroom mastery goal structures to both future choice intentions and achievement. Interest value positively mediated the association between classroom mastery goal structures and future choice intentions, while it negatively mediated the relationship between classroom performance-approach goal structures and future choice intentions. Furthermore, effort cost negatively mediated the relationship between classroom performance-avoidance goal structures and academic achievement. These findings supports the critical role of classroom environments in predicting motivational beliefs and highlight the complex interplay of different expectancy-value beliefs in shaping students’ academic success in specific learning domains.